2012
DOI: 10.2478/10004-1254-63-2012-2132
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Imidazolium Ionic Liquids on Fish and Human Cell Lines

Abstract: Ionic liquids bring a promise of a wide range of "green" applications that could replace conventional volatile solvents. However, before these applications become large-scale, their toxicity needs to be investigated in order to predict the impact on human health and environment. In this study we assessed the cytotoxicity of imidazolium ionic liquids (in the concentrations between 0.1 mmol L -1 and 10 mmol L -1 ) in the ovarian fi sh cell line CCO and the human tumour cell line HeLa using the MTT cell viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 18 publications
5
41
0
2
Order By: Relevance
“…[Tf 2 N] anion showed the highest toxic effect to CCO cells which is in correlation with results observed in HeLa cells (Stepnowski et al, 2004;Wang et al, 2007;Cvjetko et al, 2012). Some studies suggested that the increase in toxicity of ILs paired with [Tf 2 N] anion could be due to the hydrolytic cleavage that resulted in the formation of free fluoride ions (Stolte et al, 2006).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…[Tf 2 N] anion showed the highest toxic effect to CCO cells which is in correlation with results observed in HeLa cells (Stepnowski et al, 2004;Wang et al, 2007;Cvjetko et al, 2012). Some studies suggested that the increase in toxicity of ILs paired with [Tf 2 N] anion could be due to the hydrolytic cleavage that resulted in the formation of free fluoride ions (Stolte et al, 2006).…”
Section: Discussionsupporting
confidence: 84%
“…Recent studies have indicated that CCO fish cell line was good in vitro model in cytotoxicity (Tan et al, 2008) and environmental estrogens (Radošević et al, 2011). Our previous results on usefulness of CCO cells in ILs cytotoxicity testing (Cvjetko et al, 2012) encouraged us to further investigate the effects of imidazolium ILs on cellular level since such experiments on fish cells have not been performed yet.…”
Section: Introductionmentioning
confidence: 94%
“…CCO cells are slightly more sensitive to ChCl:OA than MCF-7 cells although the obtained EC 50 values are in the same range of cytotoxicity, which was consistent to our previous work on cytotoxic effects of imidazolium ILs where EC 50 did not differ much between fish CCO and human HeLa cells (Cvjetko et al, 2012). Nevertheless, it should be bared in mind that specific mechanisms of action can depend on cell type or origin of cell line and for the more comprehensive study on DESs cytotoxicity evaluation, bigger panel of cell lines would be more than desirable.…”
Section: Cytotoxicity Assessment Of Desssupporting
confidence: 93%
“…These interactions lead to disruption of membrane physiological functions, causing the leakage of cellular content and, consequently to cell death. A strong correlation between ILs toxicity and the length of the alkyl chain was found in various cell lines such as IPC-81, CCO, and HeLa (12)(13)(14), as well as in other unicellular and multicellular test organisms such as Caenorhabditis elegans (15), Escherichia coli, Staphylococcus aureus, Bacillus subtilis, Pseudomonas fluorescens, Saccharomyces cerevisiae (16), Scenedesmus quadricauda, and Chlamydomonas reinhardtii (17), Vibrio fischeri, and Daphnia magna (18). In general, the relationship between lipophilicity and toxicity is a common phenomenon called narcosis (in mammals) or basic toxicity (in aquatic organisms).…”
Section: Toxicity Mechanisms Of Ionic Liquidsmentioning
confidence: 99%